Profession of engineering ethics at work: Melamine issue as case study - Habib Khan, Md. Noman; Kabbashi, Nassereldeen Ahmed (2013)
As opposed to personal mortality, engineering ethics comes out worldwide to solve professional practice. It is an essential part of professional education because it helps students deal with issues they will face in professional practice. One way to teach engineering ethics is by using cases—not just the disaster cases that make the news, but the kinds of cases that an engineer is more likely to encounter. Many cases are available, one of those cases is a Melamine problem that hits the world when mixed up with infant mil, melamine is a fleshly compound, a based on chemical formula C3H6N6which is combined with formaldehyde to make melamine resin that is soluble in alcohol but which is not possible in water. It is classified based on its actual potential uses and exact chemical composition. Its looks like a white powder and place of origin are china (Mainland), Shandong. In China and in some food categories have been using milk power as an ingredient, like chocolate, candy, ice-cream, biscuits and eggs. The maximum people who are affected by that are infant and young children under the age of 3 years. Cyanuric acid is normally present in melamine samples and mixed together to form melamine cyanurate which can form stones in the kidney causing pain and lumb of the kidney, irreverside damage, renal failure reason to death because of uraemia. Chronic placement may reason cancer or reproductive damage. In this article, we will discuss ethically about this matter that why its increases and how we can protect our self.